Study on FSI Analysis Method of a Large Hydropower House and Its Vortex-Induced Vibration Regularities - Liaojun Zhang; Guojiang Yin; Shuo Wang; Chaonian Guan (Advances in Civil Engineering)
The working principle of a large hydropower station is to guide the high-pressure water flow to impact the turbine to rotate and generate electricity. The high-pressure water flow impacts the turbine blades, which forms complex high-speed eddy currents in the spiral case and the draft tube and causes complicated vortex-induced vibration problems. Traditionally used harmonic response methods and dynamic time-history analysis methods are difficult to reflect this complex fluid-solid dynamic coupling problem. In this paper, the bidirectional fluid-structure interaction (FSI) simulation analysis theory for a large hydropower house is studied, and the analysis methods of geometric simulation, mechanical simulation, and vibration energy transmission path simulation are presented. A large-scale 3D fluid-hydraulic machinery-concrete structure coupled model of a hydropower house is established to study the vortex-induced vibration mechanism and coupled vibration law during transient unit operation. A comparison of the fluid results against the in-site data shows good agreement. Structural responses of vibration displacement, velocity, and acceleration reveal coupled regularity of hydraulic machinery-concrete structure-fluid during blades rotating periods, and it comes to the conclusion that the turbine blade rotation is the main vibration source of the hydropower house. The research results can provide a scientific basis for the design and safe operation of the hydropower house.